2017
DOI: 10.23937/2378-3516/1410065
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chest Physical Therapy in Patients with Non-Tuberculous Mycobacteria

Abstract: Antibiotic therapy against non-tuberculous mycobacteria (NTM) is prolonged and can be associated with toxicity. We sought to evaluate whether chest physical therapy (PT) was associated with clinical improvement in patients with NTM not receiving anti-mycobacterial pharmacotherapy. A retrospective review of 77 subjects that were followed from June 2006 to September 2014 was performed. Baseline time point was defined as the first positive sputum culture for NTM; symptoms, pulmonary function, and radiology report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Previous studies have reported associations between respiratory symptoms (such as sputum and cough) and HRQOL [27], [28], and an association between the presence of a residual lesion and decreased HRQOL in patients with M. avium complex [5]. The effectiveness of airway clearance in patients with NTM-PD has been reported in several studies [29], [30], and our study showed that perioperative and post-discharge physical therapy improved the HRQOL of patients with symptomatic NTM-PD. The present ndings indicate that surgical treatment and comprehensive physical therapy of patients strongly contributed to exercise capacity and HRQOL improvement.…”
Section: Discussionsupporting
confidence: 71%
“…Previous studies have reported associations between respiratory symptoms (such as sputum and cough) and HRQOL [27], [28], and an association between the presence of a residual lesion and decreased HRQOL in patients with M. avium complex [5]. The effectiveness of airway clearance in patients with NTM-PD has been reported in several studies [29], [30], and our study showed that perioperative and post-discharge physical therapy improved the HRQOL of patients with symptomatic NTM-PD. The present ndings indicate that surgical treatment and comprehensive physical therapy of patients strongly contributed to exercise capacity and HRQOL improvement.…”
Section: Discussionsupporting
confidence: 71%
“…In addition to pharmacological therapy, other non-pharmacological measures can be tried for treating the underlying lung disease 184 These include techniques for mucus clearance such as nebulization using hypertonic saline, aerobic exercises, chest physiotherapy, postural drainage, use of oscillating positive expiratory pressure devices and high-frequency chest wall oscillation. Intake of balanced diet containing adequate calories and proteins to maintain ideal body weight is essential in the management of NTM diseases 185 .…”
Section: Treatment Of Ntm Diseasementioning
confidence: 99%
“…Patients should be advised to pay special attention to maintain adequate calorie intake and body mass index especially if surgical intervention is contemplated. Monitoring of pre-albumin level can serve as a useful marker of nutrition 184 . In some individuals along with antibiotic regimen, probiotic therapy can be helpful.…”
Section: Preventionmentioning
confidence: 99%
“…[ 44 ] In a previous study, [ 45 ] patients with NTM-PD showed high levels of depressive symptoms, and cough was found to be an important predictor of the clinical symptoms of depression. Chest physiotherapy, a nonpharmacological intervention, has been reported to reduce the symptoms of cough and phlegm, improve pulmonary function in patients with NTM-PD, [ 46 ] and may also help to improve depressive symptoms. However, whether chest physiotherapy improves pain in patients with NTM-PD is unclear and requires further investigation.…”
Section: Discussionmentioning
confidence: 99%